Power law fluid viscometry through capillary filling in a closed microchannel - Morhell, N.; Pastoriza, H. (Elsevier, 2016)
Fil: Morhell, N. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina